2012
DOI: 10.1007/s11682-012-9157-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resting state network functional connectivity abnormalities in mild traumatic brain injury

Abstract: Several reports show that traumatic brain injury (TBI) results in abnormalities in the coordinated activation among brain regions. Because most previous studies examined moderate/severe TBI, the extensiveness of functional connectivity abnormalities and their relationship to postconcussive complaints or white matter microstructural damage are unclear in mild TBI. This study characterized widespread injury effects on multiple integrated neural networks typically observed during a task-unconstrained "resting sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
148
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 113 publications
18
148
0
1
Order By: Relevance
“…Recently added 6,22,23 to the conventional MRI techniques used in clinical TBI studies, [24][25][26][27] FC has just begun to investigate potential damage to specific interregional neural connections generated by mild to moderate TBI. 6,28,29 rsFC imaging, in the present study, detected discrete differences in connectivity strength between selective brain areas of the rats with TBI from the time of initial injury to the study end-point. Consistent with our cognitive behavioral measurement, disrupted connectivity was observed immediately after injury.…”
Section: Discussionsupporting
confidence: 55%
“…Recently added 6,22,23 to the conventional MRI techniques used in clinical TBI studies, [24][25][26][27] FC has just begun to investigate potential damage to specific interregional neural connections generated by mild to moderate TBI. 6,28,29 rsFC imaging, in the present study, detected discrete differences in connectivity strength between selective brain areas of the rats with TBI from the time of initial injury to the study end-point. Consistent with our cognitive behavioral measurement, disrupted connectivity was observed immediately after injury.…”
Section: Discussionsupporting
confidence: 55%
“…This linkage supports the assumption that ICN function is vulnerable to the effects of mTBI, considering that diffuse axonal injury (DAI) usually damages long-distance white-matter tracts that connect key brain areas (known as hubs) in these networks (Smith et al, 2003;Gentleman et al, 1995). ICN abnormalities after TBI have been widely observed in resting-state fMRI, demonstrating both increase and decrease of connectivity in a number of networks, including the default mode network (DMN) and salience network (SN) (Sharp et al, 2011;Stevens et al, 2012). Several studies have also reported that these abnormalities correlate with cognitive impairment or post-concussive symptoms (Messe et al, 2013;Caeyenberghs et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…30 Modular network organization may be of particular importance for patients with acquired brain injuries. Theoretical work suggests that modularity constrains the flow of information across the brain 2 and enhances the ability of networks to rapidly reconfigure in response to environmental influences and tasks.…”
Section: Discussionmentioning
confidence: 99%